Vertical Proportion of Face in Bangladeshi Young Adult (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Introduction: Anthropometry is applied to obtain measurements of living subjects for identifying age, stature and various dimensions related to particular race or an individual. Balance in physical proportions is one the most important criteria for ideal esthetics. There are various facial heights like upper facial height (UFH), middle facial height (MFH) and lower facial height (LFH). Facial features including proportionate facial height   play a vital role in esthetics.Objectives: To evaluate the correlation among the various facial heights (UFH, MFH and LFH), the validity of vertical balance of face(upper facial height, middle facial height and lower facial height are equal) and variations in Bangladeshi adults.Materials and method: The study was a descriptive observational cross sectional study with 500 participants by convenient sampling aged 18-25 years of equal sex distribution. Each participant was made to sit on a wooden chair. The anthropometric landmarks the trichion (tri), glabella (g), subnasale (sn) and gnathion (gn), were marked on the participant’s face with a dermographic pen. With the help of a digital vernier sliding calipers, the measurements were taken in millimeters and the participant was in centric relation when measuring the facial height. Chi square test was done for gender significance. Paired “T’’ and Pearson’s correlation coefficient test were used for individual for combination of TBH to UFH, MFH and LFH to find out correlation among them. The criteria for statistical significance were set at p< 0.05 and CI 95%.Results: In males TFH, LFH, MFH & UFH were 193.2 ± 9.5 mm, 69.6 ± 3.5 mm, 66.8 ± 3.0 mm, 61.6 ± 6.2 mm  whereas in females 180.1 ±  7.9 mm, 62.7 ±  3.0 mm, 61.7 ± 2.4 mm, 55.8 ± 5.2 mm respectively. Chi square test denoted statistical significance revealing a “p” value of 0.0001 for gender significance.  Paired “T’’ was used for individual intervals for combination of TFH to  UFH, MFH & LFH and statistical significance was observed in combination of TFH to LFH,MFH &UFH with a “p” value of 0.0001 & 95 % CI. Moderate to strong statistical significant correlation was found TFH, LFH, MFH& UFH except in UFH for both males in Pearson’s correlation coefficient test.Conclusions: Our study doesn’t match the facial proportions based on artistic norms, which is being practiced in clinical orthodontics till today. Lower facial height is usually a little greater than middle facial height which is in turn greater than upper facial heightBan J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P. 1-7